Peningkatan produksi jamur tiram putih (Peurotus ostreatus L.) dengan pemberian POC rebung bambu aur - Febrianti, Irene; Gau, Seni Randa; Pandung, Natalia; Gallang, Raymon Tandi; Yusuf, Dhedhe; Pata'dungan, Adewidar Marano; Tandirerung, Willy Yavet; Limbongan, Yusuf La'lang; Galla, Ernytha Anita; Karuru, Sakti Swarno (Universitas Musamus, Merauke, Papua, 2025)
This study aims to analyze the manufacture of Liquid Organic Fertilizer (POC) from fermented bamboo shoots using leri water (rice water), molasses, and EM4, and to apply it to white oyster mushrooms. The study was conducted from July to December 2024 at the Experimental Garden of the Faculty of Agriculture, Toraja Christian University, located in Tallunglipu District, North Toraja Regency. This study used a Randomized Block Design (RAK) with three replications and five treatment levels, namely the concentration of POC bamboo shoots: R0 = 0% (control), R1 = 10%, R2 = 20%, R3 = 30%, and R4 = 40%. Each treatment consisted of three replications, with each replication using 25 baglogs. Thus, the total number of baglogs used in this study was 75 baglogs. Based on the research results, the provision of POC bamboo shoots significantly affected the growth and production of oyster mushrooms, especially in terms of mushroom fruit body weight, number of caps, cap diameter, stem diameter, and total number of pinheads. In addition, economic analysis shows that the POC bamboo shoots and products made using leri water (rice water), brown sugar, and EM4 have an excellent sales value prospect to be developed in the agricultural sector. This is supported by the availability of raw materials that are easily obtained and affordable for all groups. Farming efforts in making this POC also provide convenience for farmers in overcoming plant nutrition problems and improving the condition of the planting media and humidity. Thus, POC bamboo shoots not only increase oyster mushroom productivity but also have the potential to be developed as an environmentally friendly and economical agricultural solution.